PROFIL DAN HUBUNGAN KERJASAMA ANTARA PENGUSAHA PAPAN BUNGA DI PEKANBARU - Muhammad Sadik; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Pekanbaru. The aim of the research is to see how cooperation relationships between florist board entrepreneurs in Pekanbaru. The sample technique is Random Sampling. The writer use to quantitative descriptive methods and the data instrument are observations, questionnaire, and documentation. That the relationships of social cooperation among the florist board entrepreneurs is Mediocre, which is marked by cooperation in providing loans either money or things to helped who are full order or minimal order to other florist board. That the strategy in maintaining the florist board for entrepreneurs is Poor, which is marked by the existence of competition in getting the order, so that will cause the florist board in Pekanbaru to suffer and difficulty, and then the relationships florist board in Pekanbaru is Good. That the competition between florist board in Pekanbaru Is Fair, which is marked if the florist board entrepreneur sustained full order, so they will be to take over to others florist board entrepreneurs.Key words: cooperation, competition, florist board entrepreneurs in Pekanbaru.